Análise de de sistemas de distribuição com modelagem de geradores eólio-elétricos dos tipos I, II e IV - Galdino, Francisco Clebson Sousa (Universidade Federal Rural do Semi-Árido, 2015)
In power distribution systems are the major causes of voltage imbalances, variations in single-phase loads cause the currents in the conductors of the three phases is different, resulting in different voltage drops, causing imbalance. The study of voltage imbalances in the distribution of energy is very important, since the proper functioning of equipment connected to the system is directly related to the mains imbalance factor. When it comes to stress profiles, has become one of the biggest challenges of electric utilities, which is to serve consumers and customers with adequate voltage levels to those required in current legislation in Brazil has the 2001 resolution no. 505 ANEEL (National Electric Energy Agency) stating that the voltage to be contracted with the utility or the ONS should be between 95% (0.95 pu) and 105% (1.05 pu) of the nominal operating voltage system at the delivery point. In relation to electrical losses, although not established limits by law, these are an important economic factor for electric utilities, seeking to reduce them to maximize their profits. When it comes to connecting wind turbines to the distribution systems is not aware of scholarly conducting parallel operating conditions of the various components that operate in this plan when they are working together with the different configurations of wind generators. The objective of this study is to analyze the imbalances problem, tensions profiles and electrical losses in distribution systems by various operating situations, especially with the inclusion of wind turbines type I, II and IV, based on the system 13 bars IEEE. Also, are proposed and simulated some ways to reduce imbalances and losses through the use of engineering techniques: as promoting the balancing system loads, connecting wind farms to the distribution feeder, installing banks of single-phase voltage regulators at substations and correcting the power factor of the generator turbines. Technical proposals to reduce the levels of network imbalance are effective and also influenced the reduction of overall system losses and improve the levels of stress profiles and are therefore measures that may contribute to the proper functioning of a power system
Analysis of distribution systems modeling wind generators of types I, II and IV
Keywords: Three-phase load flow; Three-phase modeling: Wind farms; The distribution system; Three-phase wind generator; Fluxo de carga trifásico; Modelagem trifásica; Parques eólicos; Sistema de distribuição; Gerador eólico trifásico; ENGENHARIAS::ENGENHARIA ELETRICA